Effects of an ionic liquid as an additive on the thermal denaturation/degradation of lysozyme crystals. Issue 2 (17th October 2014) - Wang, Zhanzhong; Fang, Wenzhi; Li, Lijie; Li, Yan; Yu, Xiaoting; Gu, Qing; Zhou, Fengjuan
Abstract Ionic liquids (ILs) have biomaterial applications and are used for protein crystallization. The present study explores the thermal denaturation and degradation kinetics of the lysozyme crystals induced by IL [C4mim]Cl using differential scanning calorimetry (DSC). Lysozyme crystals were scanned from 10 to 250 °C at different heating rates varying from 5 to 20 °C min−1. Under the same heating rate, the addition of the IL makes lysozyme crystals confer more resistance to thermal denaturation and change values of conversion rate increase. The denaturation and degradation peak shifted towards higher temperature as heating rate increased and showed an activated denaturing kinetics of the lysozyme. It can be clearly noticed that the addition of the IL increases activation energy for denaturation and decreases it for degradation. The effect of the IL on thermal denaturation is attributed to the change of lysozyme–lysozyme molecular interaction. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.